Projected Urbanization Impacts on Surface Climate and Energy Budgets in the Pearl River Delta of China - Chunhong Zhao; Qunou Jiang; Zhongxiao Sun; Haiyue Zhong; Shasha Lu (Advances in Meteorology)
The climate impacts of future urbanization in the Pearl River Delta (PRD) region in China were simulated with the Dynamics of Land Systems (DLS) model and the Weather Research and Forecasting (WRF) model in this study. The land use and land cover data in 2000 and 2020 were simulated with the DLS model based on the regional development planning. Then the spatial and temporal changes of surface air temperature, ground heat flux, and regional precipitation in 2020 were quantified and analyzed through comparing simulation results by WRF. Results show that the built-up land will become the dominant land use type in the PRD in 2020. Besides, the near-surface air temperature shows an increasing trend on the whole region in both summer and winter, but with some seasonal variation. The urban temperature rise is more apparent in summer than it is in winter. In addition, there is some difference between the spatial pattern of precipitation in summer and winter in 2020; the spatial variation of precipitation is a bit greater in summer than it is in winter. Results can provide significant reference for the land use management to alleviate the climate change.